2013
DOI: 10.1002/hyp.9909
|View full text |Cite
|
Sign up to set email alerts
|

Modelling how vegetation cover affects climate change impacts on streamflow timing and magnitude in the snowmelt‐dominated upper Tuolumne Basin, Sierra Nevada

Abstract: Abstract:We investigated, through hydrologic modelling, the impact of the extent and density of canopy cover on streamflow timing and on the magnitude of peak and late summer flows in the upper Tuolumne basin (2600-4000 m) of the Sierra Nevada, California, under current and warmer temperatures. We used the Distributed Hydrology Soil Vegetation Model for the hydrologic modelling of the basin, assuming four vegetation scenarios: current forest (partial cover, 80% density), all forest (uniform coverage, 80% densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 108 publications
2
47
0
Order By: Relevance
“…DHSVM is a physics‐based hydrologic model used extensively in the hydrological community for a wide variety of hydrologic applications, including mountain snow process modeling (Cao et al, ; Cristea et al, ; Storck & Lettenmaier, ; Sun et al, , ; Thyer et al, ). DHSVM simulates snow accumulation and melt with a two‐layer canopy submodel and a two‐layer ground (below canopy) snow submodel.…”
Section: Methods and Datamentioning
confidence: 99%
“…DHSVM is a physics‐based hydrologic model used extensively in the hydrological community for a wide variety of hydrologic applications, including mountain snow process modeling (Cao et al, ; Cristea et al, ; Storck & Lettenmaier, ; Sun et al, , ; Thyer et al, ). DHSVM simulates snow accumulation and melt with a two‐layer canopy submodel and a two‐layer ground (below canopy) snow submodel.…”
Section: Methods and Datamentioning
confidence: 99%
“…There has been growing recognition over the last century that snow accumulation and ablation in mountain forest environments depend critically on forest structure (Broxton et al, ; Connaughton, ; Moore & McCaughey, ; Pomeroy, Parviainen, Hedstrom, & Gray, ; Varhola, Coops, Weiler, & Moore, ). Despite climate and topographic impacts of varying degrees, many studies found that forested areas, in contrast to open areas, commonly accumulate less snow and thus produce less water available for runoff, due mainly to canopy interception and evapotranspiration of up to 60% of accumulated snow (Cristea, Lundquist, Loheide, Lowry, & Moore, ; Hedstrom & Pomeroy, ; Marks, Kimball, Tingey, & Link, ; McCabe & Clark, ; McCabe, Hay, & Clark, ; Pomeroy et al, ; Regonda, Rajagopalan, Clark, & Pitlick, ; Stednick, ; Stewart, Cayan, & Dettinger, ; Troendle & King, ). Prior studies generally agree that sparser forest canopy advances melt due to reduced radiation attenuation (Link & Marks, ; Troendle & King, ; Varhola et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, previous studies showed that vegetation affects snow accumulation by interception and sublimation, and affects snowmelt by alerting the energy balance of land surface [64][65][66]. However, the relationship between snow and vegetation is highly variable and complicated, depending on climatic, topographic and vegetation conditions [65,67,68]; On the other hand, vegetation modifies runoff yield mainly by interception and ET [69,70].…”
Section: Effects Of Climate and Land Cover Changesmentioning
confidence: 99%